JURIDICAL IMPLICATIONS OF THE LEGAL NORM VOID OF INTERFAITH MARRIAGES IN INDONESIA - Indrayanti, Kadek Wiwik; Suhariningsih, Suhariningsih; Aprilianda, Nurini; Ruba’i, Masruchin (Brawijaya Law Journal, 2017)
Legal void of interfaith marriages in Indonesia to date has not offered legal certainty and sense of fairness to couples of differing religions. Particularly, their rights to form a family and to freedom of religion are unprotected; whereas those rights are guaranteed by the 1945 Constitution of the Republic of Indonesia. Furthermore, the Constitutional Court’s ruling had rejected Judicial Review on Article 2 section 1 of Law No. 1 of 1974 against the 1945 Constitution of the Republic of Indonesia. The consideration provided by the Bogor District Court regarding the rejection was that the judge’s interpretation of article 2 section 1, yielded the assertion that marrying couples should have been of the same faith. The judge also took into consideration the religious values embraced by the prospective applicant who happened to be a Catholic widow while the prospective groom was a Muslim. A similar consideration was made by the Constitutional Court where in, among others, it was stated that the constitutional rights of marriage entailed the obligation to respect the constitutional rights of other people. Therefore, to avoid any conflicts in the implementation of those constitutional rights, it is necessary to have a regulation on the implementation of constitutional rights conducted by the state.Consequently, the juridical implications of interfaith marriage legal norm void give rise to the judges’ differing interpretations which are unfavorable to interfaith couples. The validity of these marriages cannot be accomplished, resulting in the marriages to be deemed invalid, implicating the status and position of women and children as well as heritance issues.